Pengaruh Kepemimpinan Transformasional, Pemahaman Kurikulum dan Motivasi Kerja, terhadap Kinerja Guru Berdasarkan Budaya Sekolah : The Influence of Transformational Leadership, Curriculum Understanding and Work Motivation on Teacher Performance Based on School Culture - Sidik, Ramadhan; Supriadi, Didi; Saryanto, Saryanto (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
The principal's transformational leadership style is a significant factor in improving teacher work effectiveness. In addition to transformational leadership, a deep understanding of the curriculum is crucial for teachers in carrying out their duties. Work motivation is also a key factor that contributes to improving teacher performance. This study examines the relationship between school culture, transformational leadership, and teacher performance in the Special Sports Class (KKO) in Bantul Regency at the junior high school level. This study uses a quantitative survey method involving 114 teachers from five Special Sports Class (KKO) schools at the junior high school level in Bantul Regency. Data collection was carried out using a Likert-based questionnaire, and data analysis was carried out using SmartPLS to test the relationship between the variables studied. The results of the study indicate that work motivation has a significant effect on teacher performance.Meanwhile, transformational leadership and curriculum understanding do not have a significant direct effect on teacher performance. However, school culture is a mediator that strengthens the relationship between these variables and teacher performance. The implications of this study provide practical insights for policymakers in the field of education, especially in developing strategies to improve the effectiveness of principal leadership and create a school environment that supports teacher professional growth. Principals are expected to adopt a more effective transformational leadership style by providing teachers with support, inspiration, and intellectual stimulation. In addition, strengthening a positive school culture through cooperation, communication, and appreciation of teacher achievement is a strategic step to improve teacher motivation and overall performance.